СРАВНЕНИЕ ВЛИЯНИЯ ДЛИТЕЛЬНОЙ ТЕРАПИИ, ОСНОВАННОЙ НА КАРВЕДИЛОЛЕ И БИСОПРОЛОЛЕ, НА МЕТАБОЛИЧЕСКИЕ ПАРАМЕТРЫ И ЭРЕКТИЛЬНУЮ ФУНКЦИЮ У БОЛЬНЫХ АРТЕРИАЛЬНОЙ ГИПЕРТОНИЕЙ И ИЗБЫТОЧНОЙ МАССОЙ ТЕЛА ИЛИ ОЖИРЕНИЕМ: РЕЗУЛЬТАТЫ РАНДОМИЗИРОВАННОГО, ОТКРЫТОГО, ПАРАЛЛЕЛЬ - S. Y. Martsevich; S. N. Tolpygina (Klinicist, 2014)
Aim — to compare the antihypertensive efficacy, effect on blood glucose, uric acid, index of insulin resistance levels, lipid profile and effect on erectile function of long-term therapy, based on carvedilol and bisoprolol in patients with AH 1−2 deg. and overweight/obesity.Materials and methods. Type of research: clinical, multicenter, randomized, open, comparative, stepped, in two parallel groups. The study included 105 patients (53 in Carvedilol gr. and 52 in Bisoprolol gr. ). 98 patients completed the 24-week course of treatment of (48 in Carvedilol gr. and 50 in Bisoprolol gr.). Average duration of the study for each patient was 23 weeks. We took into account demographic, clinicaland anamnestic data, physical examination on all visits. ECG, biochemical analysis, questionnaire IIEF (International Index of ErectileFunction) was performed initially and at 12 and 24 weeks of therapy. After randomization, patients began to receive 12.5 mg of carvedilol twice or 5 mg bisoprolol once daily. BAB dose titration was allowed, as well as sequential addition of amlodipine and/or indapamideto achieve target BP levels.Results. Both groups of patients were comparable in terms of basic clinical and demographic characteristics of the studied parametersat baseline. Age of patients ranged from 20 to 78 years. Analysis of the blood pressure dynamics during treatment showed no significant differences in the hypotensive effect of treatment (gr. 1 ΔAP V0‑6 = −29.5 ± 11.3/17.8 ± 8.4 and gr. 2 ΔAP V0‑6 = −30.4 ± 12.8/18.7 ± 8 mm Hg; p < 0.001 for both groups) and the need for the appointment of additional drugs. All patients who completed study reached target blood pressure. In both groups for 6 months of therapy, a statistically significant decrease in weight (−1.76 ± 3.3 — gr. 1 and −1.66 ± 2.5 kg — gr. 2; p < 0.001 for both groups) and BMI (−0.57 ± 1.1 — gr. 1, p = 0.001 and −0.53 ± 0.8 kg/m2 — gr. 2, p < 0.001), WC (−1.8 ± 3.2 — gr. 1, p < 0.01 and −1.4 ± 2.8 kg/m2 — gr. 2, p < 0.05) and thighs (differences between-groups were not significant). In carvedilol g. there was a significant decrease in glucose level (−0.45 ± 1.2 mmol/l; p = 0.01), uric acid (−0.05 ± 0.01 mmol/l; p < 0.001) and LDL(−0.28 ± 0.9 mmol/l; p < 0.05), as well as the downward trend in HOMA index. In bisoprolol group there was an increase of blood creatininelevel (6.35 ± 22.4 mg/dL; p = 0.05) and there was no dynamic metabolic parameters. GFR in carvedilol gr. didn’t not significantlychanged, and in bisoprolol gr. significantly decreased from 12 to 24 weeks of therapy (−3.8 ± 15.2 ml/min/1.73 m2; pV5‑6 = 0.01). Analysisof EF showed improvement in EF in carvedilol gr. as compared with baseline and with a level of 12 weeks of therapy (Δ2.4 ± 5.0; p = 0.002for general and Δ0.67 ± 2.3; p < 0.05 for EF 1−5.15). The group also observed the deterioration of the erectile function in bisoprolol gr. bythe period from 12 to 24 weeks of therapy (−1.8 ± 7.9; p < 0.1 for total and −0.73 ± 2.7; p < 0.05 for EF 1−5.15). There were no differencesin frequency and severity of adverse events between groups.Conclusions. Though antihypertensive efficacy was equal, carvedilol, in contrast to bisoprolol, had not only beneficial metabolic effects, but in case of chronic administration was able to improve erectile function in patients with hypertension and abdominal obesity.